Limitations of paperless on-line reporting of diagnostic bacteriology culture results. Issue 9 (September 1996) - Block, C; Laloum, J; Rajs, A; Stalnikowicz, R; Shapiro, M
Abstract : AIMS: To estimate the extent to which microbiology laboratory results made available on a computerised reporting system do not reach their intended destination. METHODS: Prospective observational study of 180 urine cultures submitted from patients seen at the accident and emergency department of a 250 bed university affiliated general hospital. Observations were made of: telephone requests for results; whether results were noted in patients' charts; and antibiotic administration to patients sent home. RESULTS: Results were requested/recorded for 73% of 37 patients admitted to hospital and for only 23% of 143 patients sent home (p < 1 x 10(-7)). Overall, results were more frequently recorded for patients with positive cultures (p = 0.04). When determined separately for admitted and discharged groups, this association was not shown. Three of 14 culture positive patients sent home and for whom results were not recorded received inappropriate therapy; 19 culture negative patients were given antibiotics. CONCLUSIONS: In view of the results, measures were instituted to ensure delivery of printed reports to the health care providers of patients not admitted from the accident and emergency department. Organisations operating computerised reporting systems in evolving health care settings must ensure that system design guarantees delivery of reports to all end-users. This will minimise therapeutic problems, reduce wastage of laboratory resources, and limit risks of litigation.